1996
DOI: 10.1183/09031936.96.09010047
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcoidosis: patterns of cytokine release in vitro

Abstract: This study was designed to investigate the ability of bronchoalveolar and blood mononuclear cells to produce inflammatory mediators in vitro in pulmonary sarcoidosis. Seventeen patients with pulmonary sarcoidosis (stage I n=8; stage II/III n=9) and 10 normal controls were investigated. Bronchoalveolar and peripheral blood mononuclear cells were cultured in serum-free medium, without stimulant, for 24 h, and the supernatants analysed for concentrations of interleukin (IL)-1β (IL-1β), IL-2, IL-6, tumour necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
56
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 31 publications
6
56
1
Order By: Relevance
“…Lymphocytic alveolitis is an early initiating event in the formation of granulomatous lesions [12,18], and it is well established that there is a compartmentalization of T-lymphocytes, especially CD4+ cells, within the lungs of individuals with pulmonary sarcoidosis [13,[18][19][20][21][22]. Our data indicate that there is an increase in the number of BAL cells expressing IL-2 and IFN-γ mRNA in sarcoidosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Lymphocytic alveolitis is an early initiating event in the formation of granulomatous lesions [12,18], and it is well established that there is a compartmentalization of T-lymphocytes, especially CD4+ cells, within the lungs of individuals with pulmonary sarcoidosis [13,[18][19][20][21][22]. Our data indicate that there is an increase in the number of BAL cells expressing IL-2 and IFN-γ mRNA in sarcoidosis.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, numerous studies have shown that analysis of peripheral blood fails to give a true picture of the character and magnitude of immune processes within the lung [3,5,12,13,[18][19][20][21][22]. This has been particularly evident when comparing the profile of cytokine expression within the peripheral blood and BAL fluid of individuals with sarcoidosis [3,5,13,22]. Since cells recovered by BAL have been shown to accurately reflect the alveolitis of lung diseases, including sarcoidosis [17], we chose to examine a wide range of cytokines in the local milieu as a means of investigating the histopathology of clinical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with sarcoidosis, a specific increase in CD1a-negative mDC numbers within the airways was observed. Interestingly, sarcoidosis is associated with enhanced production of interleukin-1 and -6 and TNF-a [22,23]. Thus, the observed increase in CD1a-negative mDCs might contribute to this cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, PRIOR et al [17] did not demonstrate any significant correlation between the release of in vitro cytokines by BAL cells and the clinical indices comprising pulmonary function in sarcoidosis. In the present study, an increased level of TGF-β 1 was demonstrated in BAL fluid but not in AM supernatants from patients with altered lung function compared with patients with normal lung function.…”
Section: Discussionmentioning
confidence: 99%